Dynamic spectrum sharing access technology based on blockchain - Wei WANG; Zuguang LI; Qihui WU (物联网学报)
The blockchain technology written in the smart contract has advantages of the enabling intelligent settlement,value transfer and resource sharing,which provides a new secure and trusted platform for the dynamic spectrum sharing system.Firstly,the application of blockchain technology in dynamic spectrum sharing was summarized,considering the requirements of spectrum sharing.The key problems that need to be solved when applying blockchain to the large-scale spectrum sharing system were discussed.After that,the key challenges were analyzed in depth,and corresponding key technologies and possible solutions were provided to the above problems.